2014
DOI: 10.3109/13645706.2014.893890
|View full text |Cite
|
Sign up to set email alerts
|

Solo surgery – Early results of robot-assisted three-dimensional laparoscopic hysterectomy

Abstract: Robot-assisted solo surgery laparoscopic hysterectomy is a feasible and safe procedure. Duration of surgery, hospital stay, blood loss, and complication rates are comparable to a conventional laparoscopic hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Our findings are in accordance with previous studies on robotic camera holders [3,4,7,[15][16][17][18][19]. These studies have shown that robotic camera assistance is safe and that robotic camera holders enable the ability to perform laparoscopic procedures without camera assistance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in accordance with previous studies on robotic camera holders [3,4,7,[15][16][17][18][19]. These studies have shown that robotic camera assistance is safe and that robotic camera holders enable the ability to perform laparoscopic procedures without camera assistance.…”
Section: Discussionsupporting
confidence: 93%
“…This can reduce the number of theatre staff members and could eventually lead to increased efficiency and cost reduction. Previous studies have demonstrated solo surgery with robotic camera holders to be cost beneficial [3,4,7,[15][16][17]19]. Stott et al demonstrated that the use of the Freehand camera holder was economically viable when performing laparoscopic liver resections.…”
Section: Discussionmentioning
confidence: 99%
“…Bhayani et al [5] and Tanagho et al [6] reported human test results that found that a 3D visualization system makes it easier to perform a standardized laparoscopic task than using a conventional 2D visualization system. Recently, several commercial 3D laparoscopy products have been on the markets and quite a few test results have been reported comparing the effectiveness of 3D versus 2D laparoscopic surgeries [7][8][9][10][11][12]. Some of these systems are robot-assisted [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several commercial 3D laparoscopy products have been on the markets and quite a few test results have been reported comparing the effectiveness of 3D versus 2D laparoscopic surgeries [7][8][9][10][11][12]. Some of these systems are robot-assisted [9,13]. While some wide-FoV endoscopes can reach 100-170 • FoV, they are prone to undesirable distortion [14], and may require image processing techniques to remove the distortion before the video footage can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies showed that robot-assisted surgery in benign gynecological diseases had no obvious advantage 5-7. One study showed that well-trained laparoscopic surgeons may not really benefit from 3D robot systems if 3D laparoscopy is available 8.…”
Section: Introductionmentioning
confidence: 99%